2020
DOI: 10.1016/j.future.2020.05.030
|View full text |Cite
|
Sign up to set email alerts
|

Developing accurate and scalable simulators of production workflow management systems with WRENCH

Abstract: Scientific workflows are used routinely in numerous scientific domains, and Workflow Management Systems (WMSs) have been developed to orchestrate and optimize workflow executions on distributed platforms. WMSs are complex software systems that interact with complex software infrastructures. Most WMS research and development activities rely on empirical experiments conducted with full-fledged software stacks on actual hardware platforms. These experiments, however, are limited to hardware and software infrastru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
2

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 57 publications
0
20
0
1
Order By: Relevance
“…the WRENCH framework [31], [32]) that support the WfFormat workflow instance format. In other words, these simulators take as input workflow instances in this format (either from actual workflow executions or synthetically generated) and simulate their executions.…”
Section: Wfsimmentioning
confidence: 99%
See 3 more Smart Citations
“…the WRENCH framework [31], [32]) that support the WfFormat workflow instance format. In other words, these simulators take as input workflow instances in this format (either from actual workflow executions or synthetically generated) and simulate their executions.…”
Section: Wfsimmentioning
confidence: 99%
“…We use simulators of two state-of-the-art WMSs, Pegasus [3] and Makeflow [28], as a case study for evaluation and validation purposes. These simulators are described in [32] (note that the Makeflow simulator is really a simulator of WorkQueue, an execution engine used by Makeflow). Both Pegasus and Makeflow are being used in production to execute workflows for dozens of high-profile applications in a wide range of scientific domains and on a wide range of platforms.…”
Section: Evaluating the Accuracy Of Synthetic Workflow Instancesmentioning
confidence: 99%
See 2 more Smart Citations
“…The simulator is built using WRENCH [21], a framework for implementing simulators of WMSs that are accurate and can run scalably on a single computer. In [22], it was demonstrated that WRENCH provides high simulation accuracy for workflow executions using Pegasus. To ensure accurate and coherent comparisons, all simulation results in this section are obtained for the same simulated platform specification as that of the real-world platforms that was used to obtain the real workflow instances (based on execution logs): 4 compute nodes each with 48 processors on the Chameleon testbed [19].…”
Section: Evaluating the Accuracy Of Synthetic Workflowsmentioning
confidence: 99%